FLOWER METAPHOR INSPIRATION IN FINE ARTS - Putra, Anak Agung Ramanda; Mudana, I Wayan; Bendi Yudha, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This report is written to explain the creation of a work of art with the theme "Flower Metaphor Inspiration in Fine Arts". This topic is inspired by the author's experience when he listened to stories from his friends and books that talk about the meaning of flowers. Metaphor is a figure of speech that uses words or groups of words with figurative meanings, not their real meanings, to describe something by comparing it to something else. The flower metaphor is argued here as a small part that is almost the same as a colorful life journey. This work identifies how the flower metaphor is a meaning that produces the expression of a woman's feelings through creativity and imagination in artwork. There is one work that will be produced in the form of a painting. Each work will use various techniques and media, based on the essence and principles of fine art. More specifically, this report covers how artists use artwork to express the flower metaphor that represents a woman's feelings. Thus it can be seen that every visual artwork of the flower metaphor can appear in a smile, disappointed, disappointed, broken, love. Therefore, the other side of this artwork can help to do an in-depth and interpretive analysis on this painting, and strictly speaking, this will allow to gain an understanding of the complexity of the flower metaphor that is the inspiration in this work.